2011
DOI: 10.1007/s00253-011-3500-3
|View full text |Cite
|
Sign up to set email alerts
|

S-methyl thioesters are produced from fatty acids and branched-chain amino acids by brevibacteria: focus on l-leucine catabolic pathway and identification of acyl–CoA intermediates

Abstract: Despite their importance as potent odors that contribute to the aroma of numerous cheeses, S-methyl thioesters formation pathways have not been fully established yet. In a first part of our work, we demonstrated that Brevibacterium antiquum and Brevibacterium aurantiacum could produce S-methyl thioesters using short-chain fatty acids or branched-chain amino acids as precursors. Then, we focused our work on L-leucine catabolism using liquid chromatography tandem mass spectrometry and gas chromatography-mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Lipolysis refers to the hydrolysis of triglycerides and results in the liberation of free fatty acids (FFAs) that are important precursors of catabolic reactions that produce volatile compounds that contribute to cheese quality and flavor [ 4 , 66 , 68 ]. In our metatranscriptomic data, we observed that lipid metabolism pathway expression approximately followed the same dynamics as amino acid metabolism, i.e., a strong increase from day 1 to day 7 followed by a global stability or a slow decrease during the next three weeks ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lipolysis refers to the hydrolysis of triglycerides and results in the liberation of free fatty acids (FFAs) that are important precursors of catabolic reactions that produce volatile compounds that contribute to cheese quality and flavor [ 4 , 66 , 68 ]. In our metatranscriptomic data, we observed that lipid metabolism pathway expression approximately followed the same dynamics as amino acid metabolism, i.e., a strong increase from day 1 to day 7 followed by a global stability or a slow decrease during the next three weeks ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Brevibacterium spp. isolated from hard-type Beaufort cheese produced S -methyl thioesters using short-chain fatty acids or branched-chain amino acids as precursors ( Rattray and Fox, 1999 ; Sourabié et al, 2012 ). Deetae et al (2007) validated that the Brachybacterium strain isolated from surface-ripened cheese produced high amounts of ketones on casamino acid medium.…”
Section: Discussionmentioning
confidence: 99%
“…Some VSCs are produced as secondary volatiles via the production of hydrogen sulfide or methanethiol. Indeed, these two compounds are important precursors for subsequent VSCs synthesis (Schulz and Dickschat, 2007; Sourabié et al, 2012). Within the B. subtilis group, multiple VSCs such as dimethyl disulfide (DMDS), dimethyl trisulfide (DMTS), S -methyl thioacetate or S -methyl butanethioate have been characterized for their antifungal and nematicidal activities (Coosemans, 2005; Gerik, 2005; Gu et al, 2007; Kai et al, 2009; Wang et al, 2009; de Vrieze et al, 2015; Schmidt et al, 2015; Velivelli et al, 2015; Gotor-Vila et al, 2017).…”
Section: Volatilesmentioning
confidence: 99%